Intra-generational externalities and inter-generational transfers - Martin Kolmar; Volker Meier (Center for Economic Studies and ifo Institute (CESifo), 2005)
In an environment with asymmetric information the implementation of a first-best efficient Clarke-Groves-Vickrey (D?Aspremont-Gérard-Varet) mechanism may not be feasible if it has to be self-financing. By using intergenerational transfers, the arising budget deficit can generally be covered in every generation if the growth rate of the economy is positive. This result yields an alternative explanation for the existence of pay-as-you-go financed transfer mechanisms.
Keywords: H55; H23; D82; 330; pay-as-you-go; externalities; mechanism design; adverse selection; Umlageverfahren; Privater Transfer; Externer Effekt; Generationenbeziehungen; Adverse Selection; Asymmetrische Information; Pareto-Optimum; Theorie